Devising a method for determining the coordinates of an unmanned aerial vechicle via a network of portable spectrum analyzers - Khudov, Hennadii; Makoveichuk, Oleksandr; Kostyria, Oleksandr; Butko, Ihor; Poliakov, Andrii; Kozhushko, Yaroslav; Yarovyi, Serhii; Serdiuk, Oleksii; Mynko, Petro; Khudov, Rostyslav (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this study is the process of determining the coordinates of unmanned aerial vehicles. The study hypothesis assumed that the use of a network of portable spectrum analyzers could make it possible to detect the signals of the on-board systems of an unmanned aerial vehicle and reduce the mean square error in determining its coordinates. A method for determining the coordinates of an unmanned aerial vehicle using a network of portable spectrum analyzers has been improved, which, unlike known ones, allows for the following: – using signals of on-board equipment of an unmanned aerial vehicle; – using a network of portable spectrum analyzers; – application of both the triangulation and the difference-ranging method for determining the coordinates of an unmanned aerial vehicle by a network of portable spectrum analyzers; – carrying out spectral analysis of the signals of the on-board systems of the unmanned aerial vehicle (carried out additionally if necessary). Experimental studies have shown the capabilities of a portable spectrum analyzer to receive signals and display their spectra and spectrograms. The accuracy in determining the coordinates of an unmanned aerial vehicle by a network of portable spectrum analyzers was evaluated. It has been established: – the use of a network of portable spectrum analyzers significantly reduces the root mean square error in measuring the coordinates of an unmanned aerial vehicle by approximately 50 % compared to the error of one portable spectrum analyzer; – as the distance from the network elements of portable spectrum analyzers increases, the mean square error increases. – the use of a network of portable spectrum analyzers reduces the root mean square error in determining the coordinates of an unmanned aerial vehicle by an average of 2.29–2.62 times compared to the radar P-19MA, depending on the range